THE ROLE OF SOCIAL MEDIA IN OUR LIVES - Кодирова Барно Анваровна (TADQIQOTLAR.UZ, 2024)
Social media has become a popular part of everyday life. Millions of people use platforms like Facebook, Instagram, and Twitter to share their thoughts, connect with friends, and discover new ideas. But while social media offers many benefits, it also brings some challenges.